Localized versus systemic granulomatosis with polyangiitis: data from the French Vasculitis Study Group Registry. (20th September 2021) - Iudici, Michele; Pagnoux, Christian; Courvoisier, Delphine S; Cohen, Pascal; Néel, Antoine; Aouba, Achille; Lifermann, François; Ruivard, Marc; Aumaître, Olivier; Bonnotte, Bernard; Maurier, François; Le Gallou, Thomas; et al.
Abstract: Objective: To describe the main features at diagnosis and evolution over time of patients with localized granulomatosis with polyangiitis (L-GPA) compared with those of systemic GPA (S-GPA). Methods: EULAR definitions of L-GPA, i.e. upper and/or lower respiratory tract involvement, and S-GPA were applied to patients from the French Vasculitis Study Group Registry. L-GPA and S-GPA patients' characteristics at diagnosis and long-term outcomes were analysed and compared. Results: Among the 795 Registry patients, 79 (10%) had L-GPA. Their main clinical manifestations were rhinitis, lung nodules, sinusitis and otitis. L-GPA vs S-GPA patients at diagnosis, respectively, were younger, more frequently had saddle nose deformity or subglottic stenosis and were less often PR3-ANCA–positive. L-GPA vs S-GPA induction therapy less frequently included CYC but more often a combination of MTX and glucocorticoids; 64% of MTX-treated patients experienced disease progression within 18 months post-diagnosis. L- and S-GPA patients' estimated relapse-free–survival probabilities, relapse rates and refractory disease rates at each time point were comparable, but L-GPA patients had more frequent ENT and lung relapses, and higher overall survival rates ( P< 0.02). Over a median follow-up of 3.5 years, 18 (22.8%) L-GPA progressed to S-GPA, either as a relapse after a period in remission or more frequently in the context of refractory disease. L-GPA patients experienced more ENT-related damage. Conclusions: The relapse risks of L-GPA and S-GPA were similar, but relapse patterns differed and L-GPA overall survival rate was higher. About one-quarter of L-GPA patients developed S-GPA over time, but without end-stage organ involvement.